Pivotal Trial of the Neuroform Atlas Stent for Treatment of Anterior Circulation Aneurysms: One-Year Outcomes. Issue 7 (July 2020) - Zaidat, Osama O.; Hanel, Ricardo A.; Sauvageau, Eric A.; Aghaebrahim, Amin; Lin, Eugene; Jadhav, Ashutosh P.; Jovin, Tudor G.; Khaldi, Ahmad; Gupta, Rishi G.; Johnson, Andrew; Frei, Donald; Loy, David; et al.
Abstract : Background and Purpose: Stent-assisted coil embolization using the new generation Neuroform Atlas Stent System has shown promising safety and efficacy. The primary study results of the anterior circulation aneurysm cohort of the treatment of wide-neck, saccular, intracranial, aneurysms with the Neuroform Atlas Stent System (ATLAS trial [Safety and Effectiveness of the Treatment of Wide Neck, Saccular Intracranial Aneurysms With the Neuroform Atlas Stent System]) are presented. Methods: ATLAS IDE trial (Investigational Device Exemption) is a prospective, multicenter, single-arm, open-label study of wide-neck (neck ≥4 mm or dome-to-neck ratio <2) intracranial aneurysms in the anterior circulation treated with the Neuroform Atlas Stent and approved coils. The primary efficacy end point was complete aneurysm occlusion (Raymond-Roy class 1) on 12-month angiography, in the absence of retreatment or parent artery stenosis (>50%) at the target location. The primary safety end point was any major stroke or ipsilateral stroke or neurological death within 12 months. Adjudication of the primary end points was performed by an independent Imaging Core Laboratory and the Clinical Events Committee. Results: A total of 182 patients with wide-neck anterior circulation aneurysms at 25 US centers were enrolled. The mean age was 60.3±11.4 years, 73.1% (133/182) women, and 80.8% (147/182) white. Mean aneurysm size was 6.1±2.2 mm, mean neck width was 4.1±1.2 mm, and mean dome-to-neck ratio was 1.2±0.3. The most frequent aneurysm locations were the anterior communicating artery (64/182, 35.2%), internal carotid artery ophthalmic artery segment (29/182, 15.9%), and middle cerebral artery bifurcation (27/182, 14.8%). Stents were placed in the anticipated anatomic location in all patients. The study met both primary safety and efficacy end points. The composite primary efficacy end point of complete aneurysm occlusion (Raymond-Roy 1) without parent artery stenosis or aneurysm retreatment was achieved in 84.7% (95% CI, 78.6%–90.9%) of patients. Overall, 4.4% (8/182, 95% CI, 1.9%–8.5%) of patients experienced a primary safety end point of major ipsilateral stroke or neurological death. Conclusions: In the ATLAS IDE anterior circulation aneurysm cohort premarket approval study, the Neuroform Atlas stent with adjunctive coiling met the primary end points and demonstrated high rates of long-term complete aneurysm occlusion at 12 months, with 100% technical success and <5% morbidity. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02340585. Abstract : Supplemental Digital Content is available in the text.